Preparation And Characterisation Of Polyacrylonitrile And Poly(Methyl Methacrylate) Grafted Chitosan - Ahmad, Faraj (1998)

(untitled)
Poly(acrylonitrile) (PAN) and poly(methyl methacrylate) were grafted onto chitosan in acidic medium by using cerium ammonium nitrate as initiator under nitrogen gas atmosphere. The grafting percentage showed dependence on initiator concentration, monomer concentration, acetic acid concentration , as well as time of the reaction and temperature of the reaction. Extent of grafting, percentage of homopolymer formation, grafting efficiency and total conversion were estimated. The highest percentage of grafting of acrylonitrile achieved was as high as